Real-world patient characteristics and treatment outcomes among nontransplanted multiple myeloma patients who received Bortezomib in combination with Lenalidomide and Dexamethasone as first line of therapy in the United States - Rohan Medhekar; Tao Ran; Alex Z. Fu; Sharmila Patel; Shuchita Kaila (BMC Cancer, 2022)
Abstract Background There is limited real-world evidence that describes patients with newly diagnosed multiple myeloma (NDMM) treated with the bortezomib, lenalidomide, and dexamethasone (VRd) triplet regimen. We evaluated patient characteristics and treatment outcomes among nontransplanted NDMM patients who received VRd as their first line of therapy (LOT) in US oncology practice settings. Methods This retrospective observational cohort study evaluated patients from the Flatiron MM Core Registry who received VRd as first LOT between November 1, 2015, and February 28, 2021. Progression-free survival (PFS) was analyzed using the Kaplan-Meier method. Associations between patient demographic and clinical characteristics and PFS were evaluated using a multivariable Cox proportional hazards model. Results A total of 2342 eligible patients with VRd as first LOT were identified (mean age, 67.0 years). Among all identified patients, 64.3% were ≥ 65 years of age, 25.5% were elderly (≥75 years), and 47.9% were frail. Among patients with available data, 21.2% had high-risk cytogenetics, and the majority had International Staging System (ISS) stage I/II disease (71.8%), and Eastern Cooperative Oncology Group performance status (ECOG PS) score 0/1 (81.2%). Median duration of therapy was 5.5 months. With median follow-up of 21.0 months, median PFS and time-to-next-treatment were 26.5 and 16.1 months, respectively. Higher risk of disease progression or death was seen in patients categorized as elderly (hazard ratio [HR] = 1.37; 95% confidence interval [CI]: 1.13-1.66 vs patients < 65 years), having high-risk cytogenetics (HR = 1.44; 95% CI: 1.19-1.75 vs standard risk), having ISS disease stages II and III (HR = 1.31; 95% CI: 1.06-1.63 and HR = 1.37; 95% CI: 1.10-1.70 versus stage I, respectively), and having worse ECOG PS score (≥2) (HR = 1.49; 95% CI: 1.22-1.81 versus functionally active patients). Conclusions The majority of patients treated with VRd in this study were ≥ 65 years of age, were ISS stage I/II, had an ECOG PS score of 0/1, and had standard cytogenetic risk. Median PFS observed in real-world practice was notably shorter than that observed in the SWOG S0777 clinical trial. In nontransplanted patients treated with VRd as first LOT, a higher risk of disease progression or death was associated with older age, having high-risk cytogenetics, worse disease stage, and worse ECOG PS score.